Pengaruh Social Media Influencer dan Fear of missing out (FOMO) terhadap Minat Investasi Cryptocurrency di Kalangan Gen Z: Studi Kasus Mahasiswa Universitas Singaperbangsa Karawang - Rachmansyah, Fachridwan; Kosasih, (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study examines the influence of Social Media Influencers and Fear of Missing Out (FOMO) on cryptocurrency investment interest among Generation Z students at Singaperbangsa University in Karawang. This research uses a quantitative approach with descriptive and verification methods, with data collection through a Likert scale questionnaire. A total of 122 respondents from the university were selected using purposive sampling method. Research variables include Social Media Influencers, FOMO, and Cryptocurrency Investment Interest, with data analyzed using SPSS for multiple regression. The results showed that both Social Media Influencers and FOMO have a significant influence on cryptocurrency investment interest. The influence of Social Media Influencers has a coefficient of 0.362 (p < 0.05), while FOMO shows a coefficient of 0.290 (p < 0.05). The model's R² value of 0.319 indicates that these two variables explain about 31.9% of the variation in investment interest. These results provide important insights into how digital media and social influence affect financial decision-making among the younger generation, especially in the rapidly growing cryptocurrency market.
Keywords: Influencer; Fear of Missing Out (FoMO); Cryptocurrency Invesment